Deformation response of AgCu interfaces investigated by in situ and ex situ TEM straining and MD simulations. (1st October 2017) - Eftink, B.P.; Li, A.; Szlufarska, I.; Mara, N.A.; Robertson, I.M.
Abstract: The mechanisms of strain transfer across Ag/Cu interfaces were determined by a combination of in situ and ex situ TEM straining experiments and molecular dynamics simulations. Minimizing the magnitude of the Burgers vector of the residual dislocation generated in the interface was the dominant factor for determining the outcome of dislocation and deformation twin interactions with both non-coherent twin and cube-on-cube interfaces. This included the unexpected finding, due to the loading condition, of deformation twin activation in the Cu layer due to the intersection of deformation twins in Ag with the interface. Deformation twin nucleation in Ag from the non-coherent twin interfaces was also explained by a Burgers vector minimization argument. Graphical abstract: Image 1